Reflections on the concept of classrom violence - Fernández Cortés, Itzíar; Pericacho Gómez, Francisco Javier; Candelas, Mario Andrés (Pulso. Revista de educación, 2011)
If we base our observations on the information that we receive from the media about the atmosphere in our schools, it would be easy to conclude that violence there has increased significantly. Students harassed and abused, and teachers scared and publicly attacked have set off the alarm bells, transmitting the presumed lack of control and violence that characterizes the social reality of schools to public opinion. But are we really looking at conclusive data? Is the social reality in our schools actually changing? How can we address this situation? After years of intensive research we can now draw on a solid knowledge base about this problem. As the concepts definition becomes clearer, intervention strategies to prevent school violence are emerging.
Keywords: Educacional Enviroment; Violence; Educacional Strategies